Constraints in Adoption of Climate Resilient Technologies in Rainfed Agro-Ecosystem - V. K., Jasna; Burman, R. Roy; Padaria, R. N.; Sharma, J. P.; Varghese, Eldho; Chakrabarty, Bidisha; Loganandhan, N.; Kumar, Sanjay (Indian Journal of Extension Education, 2016)
Climate change and food security are the two daunting present day agrarian challenges. Adaptation through climate  resilience is an undebatably accepted solution to better respond to these challenges. National Innovations in Climate  Resilient Agriculture (NICRA) is an Indian Council of Agricultural Research (ICAR) initiative launched with a focus on  making most vulnerable districts of the nation climate resilient. Since the inception of the project, a number of climate  resilient technologies have been demonstrated across the country. The present investigation was undertaken with an  objective to isolate the constraints in adoption of these technologies in rainfed agro-ecosystem. The results showed  thatOfficials evaluated technical constraints, and labour and economic constraints as the most severe than that by the  farmers.Among different technical factors, 'inadequacy of inputs' stood first with mean rank 3.87 in hindering adoption as  regarded by the farmers. But officials considered 'poor availability and accessibility of short duration drought tolerant  crop varieties' as the most severe one (mean rank is 3.3). Among labour and economic constraints, 'longer gestation period  (mean ran k=3.74) to get the returns from adopted intervention' and 'shortage of owned resources'(mean rank =3.95) were  major constraints as per the opinion of farmers and officials, respectively. 'Resistance to change the conventional  practices' was considered as the most severe by both farmers(mean rank =3.99) and officials (mean rank = 4.05) in social  and personal constraints. The findings will help in redesigning the already implemented interventions to ensure a higher  adoption by managing the constraints.
Keywords: Climate resilience; climate resilient technologies; nicra; adoption; constraints